Flashcard Aksara Sunda: Sebuah Inovasi Media Pembelajaran Untuk Sekolah Dasar - Salsabila, Revita; Saputra, Erwin Rahayu (UPI, 2021)
This study aims to determine the effectiveness of the Sundanese alphabet flashcard media. The method used in this study is the literature review method, the type of descriptive analysis research, data collection techniques by collecting various scientific sources, and data analysis techniques using interactive models. The results of this study indicate that 1) Sundanese alphabets flashcard media is a form of learning media innovation that can be used in learning activities, especially for elementary school, 2) flashcard media has advantages including attractive for children, relatively cheap, and easy used, and 3) effective flashcard media to be used in Sundanese alphabets learning activities. Thus, it can be concluded that flashcard media is one form of effective learning media innovation so that it can be used as an alternative solution for learning so that children are enthusiastic about learning Sundanese alphabets.